Community participation through cooperatives in addressing basic services the Philippine experience - Teodosio, Virginia Alon (2010)
The purpose of this paper is to examine the role of cooperatives in helping the poor to access services at the community level. In the formation of strong cooperatives, there are critical cultural factors that predicate key relationships between social capital, the building of a critical mass and the role of women.

To understand why cooperatives matter it is instructive to review the bottom-up approach embedded in cooperatives in the delivery of financial services, education, health, housing, water, electric power, transport and insurance, among others.

This paper highlights a number of best practices of cooperatives in providing social services in different sectors.
Keywords: Cooperative societies; Political participation